Sistem Informasi Inventaris Barang Di UPTD Puskesmas Kemlagi Menggunakan Metode Waterfall - Rafi Fakhruddin Rizaldi; Suhendro Busono; Arif Senja Fitrani (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
This research is motivated by rapid developments in technology and science which have a positive impact on society. UPTD Puskesmas Kemlagi, as a public health institution, faces challenges in managing inventory using manual methods and MS Excel. The aim of this research is to make it easier to monitor, maintain and analyze item acceptance by utilizing the Waterfall software development approach. Black box testing is a research approach used to assess the functionality and performance of an inventory information system being developed. The research results show that the existence of an inventory information system has succeeded in helping employees carry out their duties more easily and comfortably. The implementation of the Waterfall method has proven to be effective in increasing efficiency and performance, responding to the challenges faced by the UPTD Puskesmas Kemlagi, and making a positive contribution to the management of inventory at the health institution.